Dynamic voltage scaling on MPEG decoding - Donghwan Son; Chansu Yu; Heung-Nam Kim (Proceedings. Eighth International Conference on Parallel and Distributed Systems. ICPADS 2001, 2001)
A number of research efforts have been devoted to reduce energy consumption of a processor without impacting the performance through the use of dynamic voltage scaling (DVS). The paper presents two DVS algorithms on MPEG decoding. One is DVS with delay and drop rate minimizing algorithm (DVS-DM) where voltage is determined based on previous workload only. Another algorithm scales the supply voltage according to the predicted MPEG decoding time and previous workload (DVS with predicted decoding time or DVS-PD). Simulation results show that DVS-PD improves energy efficiency as much as 56% compared to the conventional shutdown algorithm. We also found that the amount of energy saving with DVS-PD is not affected by the fluctuation of the movie stream, but is related to the error rate of the predictor, which implies that if decoding time is predicted more accurately, the DVS algorithm can be more efficient.